Australian older persons mental health inpatient and ambulatory services in 2015–2020 – A descriptive analysis and commentary. (February 2023) - Brazel, Matthew; Allison, Stephen; Bastiampillai, Tarun; Kisely, Stephen; Loi, Samantha M; Looi, Jeffrey CL
Objective: To provide a commentary on Australian state/territory older persons mental health service (OPMHS) expenditure, inpatient and outpatient services and key performance indicators (KPIs). Method: Descriptive analysis of data from the Australian Institute of Health and Welfare (AIHW), the Australian Bureau of Statistics and the World Health Organisation. Results: Between 2015–16 and 2019–20, annual expenditure on OPMHS in Australia increased by an average of only 2.3%, compared to 2.9% for all population groups, despite an increase in the number of over 65 year olds. Per capita recurrent expenditure on OPMHS decreased by an average of 1% annually. Australia's total mental health beds increased, whereas OPMHS beds decreased, mainly due to a reduction in non-acute beds. Outcomes for OPMHS admissions were similar to other age groups, except for a longer length of stay and reduced readmission rate. Older Australians accessed ambulatory mental health care at a lower rate and had a lower rate of improvement after a completed episode. Conclusions: OPMHS expenditure has not increased at commensurate levels compared to other populations. The mental health of people aged over 65 appears to be a neglected policy priority in Australia. The Royal Commission into Aged Care Quality and Safety may herald service and expenditure changes.